PEMODELAN PEMBEBENAN GAYA PADA STRUKTUR DERMAGA DENGAN APLIKASI SAP2000 - Ahmad Syarif Sukri; Riswal Karamma (Informatics Engineering Department of Halu Oleo University, 2019)
The dock is one of the port facilities that serve as a place to dock the ship in the process of loading and unloading. This study only focuses on designing docks with Deck on Pile types. The Deck on Pile type dock structure is designed strongly against the loads that work on it both its own weight and those from the environment which include wind, waves, currents and earthquakes and the load due to activities on the dock include berthing load, mooring load, and vehicle load. In this study, an analysis of the data on the physical conditions of the field includes hydro oceanography, topography, bathymetry, ship design data and design of the pier. Dock structure design includes structural dimensions, structural strength analysis using SAP2000 application.Keywords—Pier Design, Deck on Pile, Structure DOI : 10.5281/zenodo.2783984